Let u(v) be the third derivative of -v6⁄120 - v5⁄60 - v4⁄24 - v3⁄6 + 3*v**2. Let o be u(-1). Solve 5*x + 10 + 0 = o for x.
-2
Let y(x) = -x - 3. Let r be y(0). Let b be (r/2)/(2/(-4)). Suppose -2 = -q + b. Solve 0 + q = -p for p.
-5
Let s(q) = 4*q - 1. Let b(n) = -2*n + 1. Let p© = -9*b© - 4*s©. Let a be p(5). Solve 0 = -4*z - a - 7 for z.
-3
Suppose -x - 5 = 0, -x + 0*x - 13 = -2*k. Suppose 4*h - 16 = -2*y + y, -k*h = -y - 16. Solve -b - 1 + 2 = y for b.
1
Let s be 1 - (0 + 4⁄4). Solve -3*u + s*u = 0 for u.
0
Let s be ((-4)/12)/(2/(-12)). Let d be 1/s*2⁄1. Let f be (3 - 3) + d*4. Solve -f = -w + 2*w for w.
-4
Let s = 11 + -8. Let b® = 2*r3 - 3*r - 3*rs - 5 - 3*r - 5*r**2. Let j be b(-4). Solve -j*l = -2*l - 2 for l.
2
Let y(p) = p + 22. Let n be y(-17). Solve n = 4*g - 7 for g.
3
Suppose 0*c = 5c - 30. Let o be (c-1 + 4)*-1. Let a(h) = h3 - h2 - h + 6. Let q be a(0). Solve -o = -4*s - q for s.
-1
Let q = -25 + 15. Let n be (-8 - q)*(-10)/(-4). Solve -t + n - 6 = 0 for t.
-1